Operationalizing Dialects Through Studying in Universities of Kurdistan Region - Zhino Bikhtiyar Hashim; Atif Abdullah Farhadi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
There are numerous dialects in the structure of any language, and these dialects consist of several sub-dialects. Dialects of any languages have their own characteristics, and it is significant to keep them alive. Dialects of Kurdish Language, which are specific to groups of speakers in geographical locations, deserve such attention. Thus, the main method is to operationalize dialects which entails various aspects by itself. In this study, this method has been verified through field work and surveys, the main one being studying dialects at the university level. For this purpose, the Kurdish Language Departments at selected universities in Kurdistan Region, where dialects are being taught, have been put under the spotlight. Therefore, an online survey was conducted using Kobo Toolbox for fourth year students for the academic year of 2022-2023. It was done in an attempt to investigate the modality of operationalizing dialects to discover the strengths and weaknesses in order to propose improvements for the Kurdish Language Departments. The findings showed that the process of teaching dialects has its own characteristics which distinguishes it from other modules. Both ‘prioritized’ and ‘neglected’ dialects in this process are also illustrated and the reasons behind them. Finally, the most significant elements and aspects of successful operationalizing of Kurdish language dialects are found out, in addition to identifying the strong and weak points of each of these elements.